The role of stylistic devices in composition of conceptual integrity of a literary text - Rahmatova Sitora Samadovna; Arustamyan Yana Yurevna (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article explores the role of stylistic devices in forming the conceptual integrity of a literary text. Stylistic devices, including metaphors, similes, personification, and repetition, contribute to the cohesion, coherence, and thematic depth of literary works. By analyzing their use in selected literary texts, the study demonstrates how these devices not only enhance the aesthetic and expressive qualities of the text but also support the author’s conceptual intentions. The research highlights the importance of stylistic awareness for literary analysis and creative writing.